Do high‐impact invaders have the strongest negative effects on abundant and functionally similar resident species?. (16th January 2016) - Case, Erica J.; Harrison, Susan; Cornell, Howard V.
Summary: Although invasive plants may out‐compete and cause local‐scale extirpations of resident species, it is widely observed that they cause few extinctions at larger spatial scales. One possible explanation is that highly successful invaders tend to be functionally similar to, and therefore compete most strongly with, resident species that are also relatively successful and widespread. High abundance may then protect these functionally similar residents from complete extinction over large areas despite their stronger competition with the invader. We tested this idea in a native‐rich grassland where a novel invader, Aegilops triuncialis (barb goatgrass), strongly affects community diversity at the local scale. We compared resident species abundances in paired invaded and uninvaded plots with similar soil and community characteristics and invasibility as assayed by experimentally planted Aegilops . We found that the negative effects of the invader on abundance were strongest on resident species belonging to the same functional group as the invader (annual grasses). Within grasses, multivariate functional similarity to the invader also predicted decline in abundance under invasion. However, we did not find the predicted general relationship between abundance, functional similarity to the invader, and tendency to decline under invasion. Additional factors, such as spatial heterogeneity in the invaded community, must contribute to the relative scarcity of large‐scale extinctions under invasion. Abstract : Lay Summary